Medical Immunology, 7th Edition - Virella, Gabriel (CRC Press, 2019)
This seventh edition of Medical Immunology, now in a full-color presentation, continues to provide a succinct clinical review of the human response to infection while being firmly grounded in science. The authors, distinguished and experienced educators, have been able to anticipate readers’ conceptual challenges and use illustrations, diagrams, and algorithms throughout to simplify complex concepts. With an emphasis on clinical applications, methodological advances, immunological diseases, and innovative interventions, this tried and true guide navigates readers through state-of-the-sciences technologies and demonstrates their implementation in the day-to-day clinical practice of immunology. Key Features Stresses both the basic scientific concepts and clinical correlations to medical practice. Progresses logically from normal immune function to abnormalities and clinical diseases. Reviews the diagnosis, pathogenesis, and management of autoimmune diseases in a concise, manageable and visual manner Continues to be the only current medically-focused immunology text available Provides a succinct review of human response to infection with a focus on diagnostic and clinical immunology Table of Contents Chapter 1:　Introduction Gabriel Virella Chapter　2: Leucocytes and Lymphoid Tissues: The Framework of the Immune System Gabriel Virella Chapter　3: Major Histocompatibility Complex Ellen Klohe and Janardan P. Pandey Chapter　4:　The Adaptive Immune Response: Antigens, Lymphocytes and Accessory Cells Gabriel Virella and John Sleasman Chapter　5: Immunoglobulins: Structure and Diversity Gabriel Virella Chapter　6: Immunoglobulins: Metabolism and Biological Properties Gabriel Virella Chapter　7: Genetics of Immunoglobulins: Ontogenic, Biological and Clinical Implications Janardan P. Pandey Chapter　8: Antigen-Antibody Reactions Gabriel Virella Chapter　9: The Complement System in Health and Disease Carl Atkinson